Cognitive and affective empathy in binge drinking during late adolescence - Brooke A. Lester; Nita Bislimi; Claus Lamm; Ekaterina Pronizius (PLoS ONE, 2026)
Empathy–the ability to understand and share the feelings of others–has been identified as a potential correlate of binge drinking behaviors in adolescence. Our preregistered study aimed to investigate the relationship between cognitive and affective empathy and alcohol consumption in late adolescence. Building on prior research, we predicted a dissociation of cognitive and affective empathy related to alcohol consumption. Specifically, we hypothesized that whereas a negative association between affective empathy and alcohol consumption would emerge, no significant association would be observed for cognitive empathy. To test these hypotheses, we surveyed a convenience sample of U.S. college students ( N = 116; ages 18–23; 73.28% women). The online survey comprised questions assessing drinking behavior (categorized as non-binge drinking, binge drinking, and extreme binge drinking), engagement in hazardous drinking behavior (continuous measure), and self-reported empathic traits. We found that binge drinking categories and hazardous drinking scores were closely aligned, suggesting that the two measures capture similar aspects of drinking behavior. Men reported more problematic drinking patterns than women, while women scored higher on affective empathy. Age was positively related to hazardous drinking, with participants at the upper end of the age range reporting riskier alcohol use. Contrary to our preregistered hypotheses, we found no significant relationship between affective empathy and engagement in binge drinking or hazardous drinking among late adolescents. Cognitive empathy, as predicted, was not related to the extremity of alcohol consumption. Additionally, we observed a striking pattern in our data: 20.69% of our sample indicated extreme binge drinking (EBD), which is higher than the 12% reported by a U.S. national survey conducted in 2020. While the relationship between drinking behavior and empathy may be more nuanced than expected, the observed disparity in EBD behavior emphasizes the importance of addressing its prevalence within U.S. college communities and implementing proactive measures to promote responsible alcohol consumption during late adolescence.